INTERNSHIP AND TRAINEESHIP IN COURTS - AS AN EXAMPLE OF FOREIGN EXPERIENCE, PROBLEMS AND SUGGESTIONS - Холмуродов, Хусан Дониёр ўғли (Educational Research in Universal Sciences, 2022)
This article discusses the problems of internship and traineeship in the judicial system in Uzbekistan, the issues that need to be regulated, the experience of other law enforcement agencies and foreign countries are discussed with a comparative analysis.